2019
DOI: 10.1080/2314808x.2019.1586359
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic acids ameliorate doxorubicin-induced nephrotoxicity in mice: a focus on antioxidant and antiapoptotic effects

Abstract: Doxorubicin (DXR) is a broad-spectrum anti-cancer. Doxorubicin irreversible toxicity resulting from oxidative damage limits its therapeutic use. Boswellic acids (BAs) are inhibitors of 5-lipoxygenase and have been used in traditional medicine for their powerful anti-inflammatory effects and cellular protective effects. This study tested the protecting mechanisms of BAs against nephrotoxicity induced by DXR in mice and explored their antioxidant and antiapoptotic activities in the form of immunohistochemical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
8
2
Order By: Relevance
“…with non-significant improvement in the BA higher dose concerning the lower dose of BA. The obtained result was in the same line with Sami et al [ 21 ] in which they reported the nephroprotective effect of BA with a non-significant improvement of the higher dose of BA (500 mg/kg) due to the antioxidant and antiapoptotic effect of boswellic acid.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…with non-significant improvement in the BA higher dose concerning the lower dose of BA. The obtained result was in the same line with Sami et al [ 21 ] in which they reported the nephroprotective effect of BA with a non-significant improvement of the higher dose of BA (500 mg/kg) due to the antioxidant and antiapoptotic effect of boswellic acid.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, rats that received FPN plus BA (250 and 500 mg/kg) showed significant enhancement of most seminiferous tubules’ spermatogenesis by including elongated spermatids and spermatozoa. These results were inconsistent with [ 21 ] in which they reported that the most convenient restoration of these parameters was achieved in the doxorubicin + BA 500 mg/kg group. Supporting our result, data obtained by Kruger et al [ 57 ] have reported antioxidants and chelate metals of BAs in oxidative injury pathways.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations